Living Testimonies from Acadians of Îles-de-la-Madeleine - Keppie, Christina (Port Acadie)

(untitled) (Université Sainte-Anne, 2020)
The enigmas of Acadie and Acadien have long been focal points of discussion and debate in Acadian Studies, particularly in New Brunswick, where regional ideologies persist despite a collective understanding of the impact of globalization on Acadians as a cultural minority. Unfortunately, not much place has been granted to other Acadian communities in this discussion, such as the Îles-de-la-Madeleine, whose residents are among the one million individuals of Acadian heritage currently living in Quebec. Despite outward efforts by organizations such as the Congrès mondial acadien to promote Acadie as an inclusive community, it continues to be defined and shaped by its New Brunswick elite. The current study gives voice to those Acadians less heard – les Madelinots – through a qualitative analysis of data from the 2004 collection ArtcaDit: témoignages vivants sur l’identité acadienne. This study illustrates the ideological attachment of the Madelinots to their environment and shared past over the identity pole of language, around which much discussion of acadianité is currently centered in Acadian Studies.